Promotion Effectiveness Using EPIC Model - Alexius Endy Budianto (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2017)
Competition between universities and the amount of expenditure funds that require the college to know the effectiveness of promotional activities that have been done. This study aims to determine the effectiveness of promoting the introduction of campus